Interest deviation and the Brazilian government bond yields - Azevedo, Fábio da Rocha (2022)
Central Banks have tools to benchmark their decisions over the most common monetary policy channel, the short-term interest rate. One of the most famous tools is the Taylor rule, which is based on a widely known equation that defines the short-term interest rate as a combination of the output gap, the inflation deviation of its target and the natural level of interest. By definition, depending of the macroeconomic context, the Central Banks can create a positive deviation from the natural level of interest to hold inflation to its target, while reducing the economic activity – the opposite is true. A side effect from the changes in the short-term interest rate can be linked to the changes in the long-term rates, specially from the Government bond yield. This study assesses the interest rate deviation (IRD) from its natural level affects the Brazil National Treasury Bills (LTN) yield curve. In other words, how the term structure channel reacts to of short-term monetary policy changes. The Natural Interest Rate (NIR) is estimated in three different approaches and some impulse response functions are done to evaluate how bond yields behavior after a monetary shock. It concludes that the Brazil Central Bank has adopted a conservator administration during the years evaluated, with a short- term interest rate above its natural level. Also, the changes in IRD negatively affect long-term yields, but not significantly. Lastly, this study contributes to the current literature registering a rolling regression window approach for the estimation of the natural interest rate.